Direct time domain evaluation of the transient field transmitted into a lossy ground due to GPR antenna radiation. (September 2017) - Poljak, D.; Sesnic, S.; Susnjara, A.; Paric, D.; Drissi, K. El Khamlichi; Lallechere, S.
Abstract: The paper deals with the direct time domain calculation of a transient electric field generated by a ground penetrating radar (GPR) dipole antenna and transmitted into the lossy half-space. The space–time dependent current along the dipole is governed by the Hallen integral equation which is numerically solved by means of the Galerkin–Bubnov scheme of the Indirect Boundary Element Method (GB-IBEM). Provided that the current distribution along the GPR antenna is determined, one may compute the related electromagnetic field transmitted into the lossy ground by solving the field integral formulas. Some illustrative computational examples related to the transmitted field into the lower half-space are reported in this paper.